Creating Shared Value in Upstream Oil and Gas Company and Community: A Case Study of CSR Implementation in PT Pertamina EP Tarakan Field - Kurniawan, Isrianto; Nurlaela Arief , Neneng (Journal of World Science, 2023)
This research examines a Creating Shared Value (CSV) practice trough CSR implementation in upstream oil and gas company and how it corresponds to sustainability. In a year of 2020, saw a notable natural declined in energy resources as a result of Tarakan Field production performance. This faced numerous economic and social challenge, including a responsibility to support holding company commitment to manage energy resilience as well as contribute to SDGs. This research, which incorporates information from literature analysis, in-depth interviews and company reports, shows that Tarakan Field’s CSR implementations were a useful strategy for generating shared value for business, stakeholders, and communities in line with sustainability. It makes an argument for the relationship between CSR implementation and sustainability, as well as the implementation plan and CSV measurement through CSR implementation in Tarakan Field. These concerns are particularly evident in the vague of CSV measurement which made it inefficient for the company to meet its commitment by unintegrated CSR and operation activities in spite of company strategy.